Phosphorus-containing peptides as mixed inhibitors of endopeptidase 3.4.24.15 and 3.4.24.16: effect on neurotensin degradation in vitro and in vivo. - Vincent, B. (1995)
1. We have examined several phosphorus-containing peptides as potential mixed inhibitors of two neurotensin-degrading zinc metallopeptidases, endopeptidase 3.4.24.15 and endopeptidase 3.4.24.16. 2. Among a series of 13 phosphonamide peptides, N-(2-(2-naphtyl)ethylphosphonyl-glycyl-prolyl-norleucine (phosphodiepryl 08) was found to inhibit potently the hydrolysis of neurotensin by purified endopeptidase 3.4.24.15 and 3.4.24.16 with an identical Ki value of 0.4 nM. 3. Phosphodiepryl 08 displayed a strong selectivity towards the two peptidases since it failed to inhibit several other zinc-containing peptidases such as endopeptidase 3.4.24.11, angiotensin-converting enzyme, aminopeptidase M, leucine aminopeptidase and carboxypeptidases A and B. 4. The protective effect of phosphodiepryl 08 on neurotensin degradation was examined in vitro and in vivo in central and peripheral bioassays. 5. Phosphodiepryl 08 virtually abolished neurotensin degradation by 4-day-old plated pure cultured neurones from mouse embryos and greatly potentiated neurotensin-induced antinociception in the mouse hot plate test. 6. In the periphery, phosphodiepryl 08 inhibited neurotensin degradation by membranes prepared from isolated longitudinal smooth muscle of guinea-pig ileum and greatly potentiated the neurotensin-induced contraction of the same longitudinal smooth muscle preparation. 7. Our study indicates that phosphodiepryl 08 behaves as a potent and selective mixed inhibitor of endopeptidase 3.4.24.15 and 3.4.24.16 and can be used as a powerful agent to prevent neurotensin degradation, in vitro and in vivo, in central and peripheral assays.